Integrative Self‐Sorting in a Three Component System Leading to Formation of Long Fibrous Structures. Issue 5 (29th April 2016) - Nayak, Nagaraj; Gopidas, Karical R.
Abstract: In this paper we report the integrative self‐sorting processes in a three‐component system consisting of β‐CD, a bis‐adamantane derivative AD‐AD and a bis‐pyromellitic diimide derivative PI‐PI in a 2:1:1 ratio, leading to the slow evolution of long fibers. Using TEM, AFM and time‐dependent ICD measurements of the three‐component system and the constituent two‐component systems (β‐CD/AD‐AD and β‐CD/PI‐PI), involvement of two social self‐sorting and two narcissistic self‐sorting processes, which led to the evolution of the long fibers, were identified. Initially a bis‐inclusion complex of β‐CD and AD‐AD is formed through a social self‐sorting process. The bis‐inclusion complex undergoes a narcissistic self‐assembly to give vesicles. The key step in the integrative self‐sorting is binding of PI‐PI to the vesicle surface through rim‐binding association. The rim‐binding motif is effectively exploited herein to perform the functions of vesicle recognition, and vesicle joining. Abstract : Integrative self–sorting in a three‐component system in aqueous solution is reported. The process involved social and narcissistic self‐sortings at different stages of the self‐assembly, which ultimately led to formation of long fiber‐like assemblies.